Stabilization and solidification of metal sludges - Hong, Su Sian. (2008)
With the rapid process of industrialization and advancement in technology, industrial wastes has been generating at a tremendous rate in the last few decades. The industrial sludges produced from waste treatments are usually disposed of in the landfills. In Singapore, however, the sludge disposal has become a problem due to the scarcity of land. Existing landfills are filling up fast and thus raised the need to look for other alternatives. Among the types of hazardous industrial wastes, materials containing heavy metals are of great environmental concern due to its high volume and accumulation in the environment. They are hazardous to both environment and life forms; hence it is important that these wastes are treated for safe disposal. Studies have been carried out elsewhere on the use of industrial and municipal sludge for innovative construction materials. This project explores on the possibility of using an industrial waste - Calcium Fluoride ( CaF2 ) sludge as a waste binder in the solidification /stabilization (S/S) process of heavy metal sludges.